2000
DOI: 10.1021/jm001028o
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monoamine Oxidases by Functionalized Coumarin Derivatives:  Biological Activities, QSARs, and 3D-QSARs

Abstract: A large series of coumarin derivatives (71 compounds) were tested for their monoamine oxidase A and B (MAO-A and MAO-B) inhibitory activity. Most of the compounds acted preferentially on MAO-B with IC(50) values in the micromolar to low-nanomolar range; high inhibitory activities toward MAO-A were also measured for sulfonic acid esters. The most active compound was 7-[(3, 4-difluorobenzyl)oxy]-3,4-dimethylcoumarin, with an IC(50) value toward MAO-B of 1.14 nM. A QSAR study of 7-X-benzyloxy meta-substituted 3,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
199
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(233 citation statements)
references
References 41 publications
11
199
2
1
Order By: Relevance
“…Recently, our group has published the synthesis and the biological activity of a series of 7-substitued coumarin derivatives of general structure I displaying a dual AChE/MAO inhibitory activity ( Figure 1). 13 The inhibitory potency towards the MAO, in particular the MAO-B isoform, was in the nanomolar range, whereas a lower potency, in the micromolar range, was found against AChE. The absence of protonated or quaternary nitrogen atoms in compounds I and the prevalent hydrophobic character of the substituted coumarin moieties, suggested that the inhibitory activity of I could arise from an interaction at the peripheral binding site located at the entrance of the enzymic gorge ending with the primary (anionic) binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has published the synthesis and the biological activity of a series of 7-substitued coumarin derivatives of general structure I displaying a dual AChE/MAO inhibitory activity ( Figure 1). 13 The inhibitory potency towards the MAO, in particular the MAO-B isoform, was in the nanomolar range, whereas a lower potency, in the micromolar range, was found against AChE. The absence of protonated or quaternary nitrogen atoms in compounds I and the prevalent hydrophobic character of the substituted coumarin moieties, suggested that the inhibitory activity of I could arise from an interaction at the peripheral binding site located at the entrance of the enzymic gorge ending with the primary (anionic) binding site.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Establishment of structure-activity relationship helpful in understanding the interaction of the newly designed molecule with MAO enzyme. 17 Some acetamide derivatives with potent MAO inhibiting activity were found among them safinamide was found potent MAO inhibitor.…”
mentioning
confidence: 99%
“…The chemical structures of all the compounds were elucidated by a comparison of their melting point, 1 H NMR and 13 C NMR, data with literatures. [9][10][11][12][13][14][15] Compounds 13 and 14 were biosynthesized from substrates 4 and 5 under the same process in the literature. 8) Compound 15 was identified by MS and NMR spectra.…”
mentioning
confidence: 99%